A Demodulation Algorithm for Periodically In-Plane Vibrating MEMS Based on a Stroboscopic Micro-Visual System. (February 2022) - Yu, Minhui; Sang, Mei; Guo, Cheng; Zhang, Ruifeng; Zhao, Fan; Liu, Hongguang; Liu, Tiegen
Abstract: Abstract: A high-frequency short-pulsed stroboscopic micro-visual system was employed to capture the transient image sequences of a periodically in-plane working micro-electro-mechanical system (MEMS) devices. To demodulate the motion parameters of the devices from the images, we developed the feature point matching (FPM) algorithm based on Speeded-Up Robust Features (SURF). A MEMS gyroscope, vibrating at a frequency of 8.189 kHz, was used as a testing sample to evaluate the performance of the proposed algorithm. Within the same processing time, the SURF-based FPM method demodulated the velocity of the in-plane motion with a precision of 10 −5 pixels of the image, which was two orders of magnitude higher than the template-matching and frame-difference algorithms.